Power-related determinants of modified agility t-test performance in male adolescent basketball players - Scanlan, A. T.; Wen, N.; Pyne, D. B.; Stojanovic, E.; Milanovic, Z.; Conte, D.; Vaquera, A.; Dalbo, V. J. (The Journal of Strength and Conditioning Research, 2021)
Although the Modified Agility T-test (MAT) has been advocated for assessing change-of-direction performance in basketball, the power-related attributes emphasized during the test are unknown. Therefore, the aim of this study was to identify the power-related determinants of the MAT in basketball players. A cross-sectional, descriptive research design was used whereby national- and state-level male adolescent basketball players (n = 24; 17.3 ± 0.5 years) completed a battery of power-related performance tests. The tests administered included the MAT, isometric midthigh pull, 10-m sprint, countermovement jump, 1-step vertical jump, standing long jump, and repeated lateral bound. Associations between performance during the MAT and other tests were quantified, and performance in each test was compared between faster (>50th percentile) and slower (<50th percentile) players in the MAT. The MAT exhibited large correlations (p < 0.05) with standing long jump distance (r = -0.67, R2 = 45%), countermovement jump relative peak force (r = -0.63, R2 = 39%), isometric midthigh pull relative peak force (r = -0.55, R2 = 30%), and 10-m sprint time (r = 0.53, R2 = 28%). The faster group performed better (p < 0.05) during the standing long jump (mean difference; ±90% confidence limits: 0.16; ±0.12 m) and produced greater (p < 0.05) relative peak force during the isometric midthigh pull (2.5; ±2.3 N/kg) and countermovement jump (2.1; ±1.8 N/kg) than the slower group. The MAT complements other power-related tests used in basketball and stresses basketball-specific, power-related attributes in various movement planes. These data can inform training and testing approaches to optimize change-of-direction performance in basketball.